Dash & Lily's book of dares - Cohn, Rachel; Levithan, David (Ember, 2020)
In a story told in the alternating voices of Dash and Lily, two sixteen-year-olds carry on a wintry scavenger hunt at Christmastime in New York, neither knowing quite what--or who--they will find.